Phosphatidylcholine hydrolysis activates NF-kappa B and increases human immunodeficiency virus replication in human monocytes and T lymphocytes. - Arenzana-Seisdedos, F (1993)
We have tested whether breakdown of phosphatidylcholine (PC) initiated by exogenous addition of a PC-specific phospholipase C (PC-PLC) from Bacillus cereus or by endogenous overexpression of PC-PLC induces functional activation of NF-kappa B and increases human immunodeficiency virus (HIV) enhancer activity. PC-PLC-activated hydrolysis of PC was found to induce bona fide p50/p65 NF-kappa B binding activity in three different cell lines of human or murine origin. No significant changes in the turnover of other cellular phospholipids were detected in PC-PLC-treated cells. Induction of NF-kappa B by PC-PLC did not depend on de novo synthesis of proteins or autocrine secretion of either tumor necrosis factor or interleukin 1. In human monocytic and lymphoblastoid T-cell lines, induction of NF-kappa B by PC-PLC resulted in clear induction of luciferase expression vectors placed under the control of synthetic kappa B enhancers or wild type, but not kappa B-mutated, HIV long terminal repeat constructs. HIV replication was increased by PC-PLC in chronically infected monocytes and T lymphocytes. NF-kappa B activation promoted by addition of exogenous PC-PLC correlated with an intense production of diacylglycerol. However, addition of a phosphatidylinositol-specific PLC from B. cereus also induced diacylglycerol but did not activate kappa B enhancer-directed vectors. PC-PLC-induced NF-kappa B activation could not be blocked by a specific inhibitor of phorbol ester-inducible protein kinases C. These results indicate that a cellular transduction pathway, dependent on specific PC breakdown, is functional in T lymphocytes and monocytes and may be used by various transmembrane receptors to activate HIV transcription through NF-kappa B-dependent induction of the HIV enhancer.